Enhancement of Attentional Performance by Selective Stimulation of α4β2(*) nAChRs: Underlying Cholinergic Mechanisms - Howe, William M (Nature Publishing Group, 2010)
Impairments in attention are a major component of the cognitive symptoms of neuropsychiatric and neurodegenerative disorders. Using an operant sustained attention task (SAT), including a distractor condition (dSAT), we assessed the putative pro-attentional effects of the selective α4β2(*) nicotinic acetylcholine receptor (nAChR) agonist S 38232 in comparison with the non-selective agonist nicotine. Neither drug benefited SAT performance. However, in interaction with the increased task demands implemented by distractor presentation, the selective agonist, but not nicotine, enhanced the detection of signals during the post-distractor recovery period. This effect is consistent with the hypothesis that second-long increases in cholinergic activity (‘transients') mediate the detection of cues and that nAChR agonists augment such transients. Electrochemical recordings of prefrontal cholinergic transients evoked by S 38232 and nicotine indicated that the α4β2(*) nAChR agonist evoked cholinergic transients that were characterized by a faster rise time and more rapid decay than those evoked by nicotine. Blockade of the α7 nAChR ‘sharpens' nicotine-evoked transients; therefore, we determined the effects of co-administration of nicotine and the α7 nAChR antagonist methyllycaconitine on dSAT performance. Compared with vehicle and nicotine alone, this combined treatment significantly enhanced the detection of signals. These results indicate that compared with nicotine, α4β2(*) nAChR agonists significantly enhance attentional performance and that the dSAT represents a useful behavioral screening tool. The combined behavioral and electrochemical evidence supports the hypothesis that nAChR agonist-evoked cholinergic transients, which are characterized by rapid rise time and fast decay, predict robust drug-induced enhancement of attentional performance.